Pd‐Modified De‐alloyed Au−Ni‐Microelectrodes for In Situ and Operando Mapping of Hydrogen Evolution. Issue 6 (16th March 2022) - Kund, Julian; Romer, Jan; Oswald, Eva; Gaus, Anna‐Laurine; Küllmer, Maria; Turchanin, Andrey; von Delius, Max; Kranz, Christine
Abstract: To date most studies focusing on light‐driven water splitting for green energy conversion schemes depend on bulk analyses of the produced hydrogen using, e. g ., head‐space gas chromatography. In this contribution, we present the fabrication of Pd‐modified microelectrodes for in situ electrochemical hydrogen measurements using de‐alloyed Au−Ni microelectrodes. Stability studies and pH‐dependent investigations revealed the stability of these microsensors over a period of seven days, and confirmed their applicability in a pH range of 3–10 with a limit of detection (LOD)<1 μmol/L. First in situ proof‐of‐principle electrochemical imaging of hydrogen generated at a microelectrode and operando studies of hydrogen evolution at earth‐abundant cobalt hydrogen evolution catalysts using the developed Pd‐microsensors in combination with scanning electrochemical microscopy (SECM) demonstrated the potential of these microsensors for operando studies in light‐driven heterogeneous catalysis. Abstract : In situ H2 measurement : The fabrication and calibration of an electrochemical Pd‐based hydrogen microsensor is reported. We successfully show proof of principle imaging experiments in SECM SG/TC mode for hydrogen mapping but also the quantification of light‐driven hydrogen evolution at heterogenized cobaloxime‐based HER catalysts.